Malignant peritoneal mesothelioma -- diagnostic and therapeutic difficulties. - Cunha, P (2002)
Malignant Peritoneal Mesothelioma (MPM) is an uncommon tumour. Clinical presentation is indefinite and differential diagnosis with peritoneal carcinomatosis is difficult. It has a bad prognosis (survival of 6-12 months) due to the delay of the diagnosis and inefficacy of the conventional therapeutic. The authors present a case of MPM which was diagnosed over the investigation of ascitis. The laparoscopic peritoneal biopsy permitted the diagnosis. After systemic quimiotherapy, the patient is in partial remission at 42 months of follow-up.